Segmentation of cancerous regions in liver using an edge-based and phase congruent region enhancement method. (July 2016) - Sethi, Gaurav; Saini, B.S.; Singh, Dilbag
Graphical abstract: Highlights: Novel level set method for segmenting low contrast cancerous regions is presented. Proposed method uses new stopping function based on edge and phase information. Result indicates the superiority of the proposed method in 2D and 3D CT images. Abstract: Segmenting low-contrast cancerous regions from Computed Tomography (CT) images is an important task. Region and edge-based active contours fail to perform with such images. Thus, edge-based phase congruent region enhancement is proposed for detecting low-contrast boundaries using new stopping function. The stages of the proposed method are: region separation, region enhancement and Distance Regularised Level Set Evolution (DRLSE) with new stopping function. First, cancerous region is delineated by creating phase map and converting it into an edge map by thresholding. Second, the feature map is created by enhancing features at the boundaries of edge map. The feature map is combined with original image to generate final image. Finally, stopping function is constructed for DRLSE based on the gradient of final image. Experiments were performed on 20 two dimensional and 4 three dimensional CT scans. The proposed method was compared with two active contours. Results prove the superiority of proposed method.